1990
DOI: 10.1128/jvi.64.2.962-965.1990
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of murine monoclonal antibodies to the tat protein from human immunodeficiency virus type 1

Abstract: A panel of murine monoclonal antibodies (MAbs) to the human immunodeficiency virus type 1 transactivator tat protein were characterized. The anti-tat MAbs were mapped to the different domains of the tat protein by Western blot (immunoblot) and Pepscan analyses. One-half of the MAbs tested mapped to the amino-terminal proline-rich region, and one-third of the MAbs tested mapped to the lysine-arginine-rich region of tat. The individual MAbs were tested for inhibition of tat-mediated trans activation, using a cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…An additional B cell epitope was identified between residues 46-60. These results are in agreement with previous reports in which B cell linear epitopes were identified in the murine BALB/c system [36,37]. This is an important finding, since in vitro experiments have indicated that mAb against the Nterminal activation domain of Tat protein (Tat 2-21 and Tat [4][5][6][7][8][9][10][11][12] ) and the basic region (Tat 50-62 ) inhibit HIV-1 Tatmediated LTR transactivation, and HIV-1 infection and replication in acutely and persistently infected human CD4 + cells [36,38,39].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…An additional B cell epitope was identified between residues 46-60. These results are in agreement with previous reports in which B cell linear epitopes were identified in the murine BALB/c system [36,37]. This is an important finding, since in vitro experiments have indicated that mAb against the Nterminal activation domain of Tat protein (Tat 2-21 and Tat [4][5][6][7][8][9][10][11][12] ) and the basic region (Tat 50-62 ) inhibit HIV-1 Tatmediated LTR transactivation, and HIV-1 infection and replication in acutely and persistently infected human CD4 + cells [36,38,39].…”
Section: Discussionsupporting
confidence: 94%
“…These results are in agreement with previous reports in which B cell linear epitopes were identified in the murine BALB/c system [36,37]. This is an important finding, since in vitro experiments have indicated that mAb against the Nterminal activation domain of Tat protein (Tat 2-21 and Tat [4][5][6][7][8][9][10][11][12] ) and the basic region (Tat 50-62 ) inhibit HIV-1 Tatmediated LTR transactivation, and HIV-1 infection and replication in acutely and persistently infected human CD4 + cells [36,38,39]. Of further importance is the fact that specificity against the same B cell epitopes was also found in sera of Tat-vaccinated monkeys, as well as in HIV-1-infected individuals ( [32,33] and unpublished data), and that vaccination of monkeys with peptides encompassing these epitopes was able to control chronic viremia after challenge [40].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Very interestingly, the carboxy-terminal region, amino acid residues 498-534, had an extremely high content of proline (40.5%). It has been reported that proline-rich regions exhibit high immunogenicity [15]. This molecular mass was far smaller than that estimated for the purified CSP (72-kDa) from SDS-PAGE analysis.…”
Section: Resultsmentioning
confidence: 63%